Evaluation of Financial and Credit Institutions Branches over a Period of Time with Dependent Criteria - Rouhollah Kiani Ghaleh no (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: In this research, an algorithm for evaluating and ranking the branches of a financial and credit institution is presented that can assess the performance in a period and manage the jump or stagnation of cross-sectional performance of branches. In the algorithm, the possibility of separating the criteria into two efficient and effective groups per the organization's strategy is located, which can facilitate experts' decision to select effective and weighty indicators for them. Methodology: The performance of branches in various periods is expressed as a fuzzy number. The structure of the fuzzy TOPSIS method is used in the algorithm. A new step of grouping the criteria to calculate the value of the criteria related to the fuzzy TOPSIS technique has been added, and the calculation formula has been described. Mechanism The reason for the superiority of the branches in terms of the whole to the part is expressed using the similarity matrix. Findings: The proposed algorithm ranks 51 branches of Keshavarzi Bank in Sistan and Baluchestan province. The reason for scoring the top three branches, middle and bottom of the ranking table, based on the similarity matrix, is discussed. Originality/Value: 1- Generating a decision matrix with fuzzy numbers based on the performance of multiple sections 2- Providing a structure for the possibility of separating indicators into two categories: efficient and effective 3- Formulating and weighing sub-indicators in proportion to the degree of dependence on the index head.